Is Intestinal Microbiota Fully Restored After Chickens Have Recovered from Coccidiosis? - Jiaqing Guo; Zijun Zhao; Chace Broadwater; Isabel Tobin; Jing Liu; Melanie Whitmore; Guolong Zhang (Pathogens)
The intestinal microbiota is known to be altered by Eimeria-induced coccidiosis, but it remains unclear whether the microbiota is fully restored after recovery. To address this, 110 newly hatched Cobb male broiler chickens were challenged with 2 × 104 sporulated oocysts of Eimeria maxima (EM) strain M6 or mock-infected with saline on day 10. Body weight and feed intake were recorded. Additionally, 10 mock- and 12 EM-infected birds were randomly selected to assess the small intestinal lesion, fecal oocyst shedding, and ileal and cecal microbiota compositions using 16S rRNA gene sequencing at 3, 5, 7, 14, and 21 days post-infection (dpi). EM infection significantly decreased (p < 0.001) body weight by 5 dpi, persisting through 21 dpi. The infection also reduced (p < 0.05) weight gain, feed intake, and feed efficiency in the first week; however, these parameters became comparable in the second and third weeks. At 7 dpi, during the peak of infection, major lactic acid bacteria were enriched, while short-chain fatty acid-producing bacteria were mostly suppressed in both the ileum and cecum. Opportunistic pathogens such as Escherichia and Clostridium perfringens transiently bloomed at 7 dpi. By 14 dpi, differential bacterial enrichment subsided, and nearly all commensal bacteria returned to healthy levels by 21 dpi. Coupled with comparable growth performance between healthy and EM-recovered chickens, we conclude that the intestinal microbiota is largely restored to its healthy state after recovery. Understanding the microbiota’s responses to coccidiosis may inform probiotic-based mitigation strategies.